Factors affecting reorientation of hydraulically induced fracture during fracturing with oriented perforations in shale gas reservoirs (Fracture and Structural Integrity, 2021)
Hydraulic fracturing with oriented perforations is an effective technology for reservoir stimulation for gas development in shale reservoirs. However, fracture reorientation during fracturing operation can affect the fracture conductivity and hinder the effective production of shale gas. In the present work, a numerical simulation model for investigating fracture reorientation during fracturing with oriented perforations was established, and it was verified to be suitable for all investigations in this paper. Based on this, factors (such as injection rate and fluid viscosity) affecting both of initiation and reorientation of the hydraulically induced fractures were investigated. The investigation results show that the fluid viscosity has little effect on initiation pressure of hydraulically induced fracture during fracturing operation, and the initiation pressure is mainly affected by perforation azimuth, injection rate and the stress difference. Moreover, the investigation results also show that perforation azimuth and difference between two horizontal principle stresses are the two most important factors affecting fracture reorientation. Based on the investigation results, the optimization of fracturing design can be achieved by adjusting some controllable factors. However, the regret is that the research object herein is a single fracture, and the interaction between fractures during fracturing operation needs to be further explored.
Keywords: Hydraulic fracturing; Oriented perforation; Fracture initiation; Fracture reorientation; Fracture propagation; Shale reservoir